Improvement of productivity and polysaccharide‑protein complex in Agaricus blazei - Chu, Jiunn-Nan; Young, Chiu-Chung; Tan, Chen-Chung; Wu, Szu-Pei; Young, Li-Sen (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess the productivity and polysaccharide‑protein complex content of Agaricus blazei on rice straw medium, in comparison to conventional sawdust, using four casing soils. The A. blazei strain used was BCRC36814T, purchased from the Food Industry Research and Development Institute, Hsin‑Chu, Taiwan. The two media were evaluated as to A. blazei productivity, harvesting time, and production costs. The experimental design used was a randomized complete block, with four replicates. Three local casing soils – Typic Paleudult (CCe), Typic Udorthent (Tq) and Oxyaquic Paleudult (TSp) – were compared to imported peat soil (PS, Saprists, Histosols), used as the control. The productivity of A. blazei using Tq and TSp soil was significantly higher. The TSp casing treatment resulted in earlier harvest by at least 14 to 27 days, when compared to the other treatments. The polysaccharide content in CCe (13.2%) and Tq soils (13.2%) did not differ significantly from the PS (13.4%) and TSp (10.6%) treatments. Local casing soils decreased the production costs of A. blazei cultivation. Composted rice straw can substitute sawdust as the culture medium for A. blazei production with increased yield.